Letramento funcional em saúde e fatores associados de pessoas idosas cadastradas na estratégia de saúde da família - Lima, Juliana Piveta de (2018)
With the increase in elderly population, there is a relative rise Chronic Noncommunicable Diseases, which affect mostly the elderly and are responsible for high death rate. Besides the necessary permanent care of people in chronic conditions, a more adequate and effective approach is required, using simple and clear language regarding health instruction provided for selfcare. It is important to assess Functional Health Literacy, since understanding health information can interfere in clinical outcomes, in a way that less capacity in self-management and lack of knowledge and ability related to health could hinder the adoption of healthy behavior and the prevention or management of acute and chronic diseases. The aims of this study are: characterizing the profile of acute and chronic diseases and the use of pharmaceuticals by elderly people assisted by the Family Health Strategy of the city of Rio Grande, Brazil; assessing Functional Health Literacy of elderly people assisted by Family Health Strategy; and identifying whether there is a relation between Functional Health Literacy and the variables of sociodemography, health and use of medication. The study integrates the macro project named “Relation between functional health literacy, use of medication and functionality among elderly people at Family Health Strategy”. The macro project was forwarded to the Ethics and Health Research Committee of the Federal University of Rio Grande, obtaining favorable feedback number 93/2017, and later to the City Center of Permanent Collective Health Education of the Health City Department of Rio Grande, Brazil, obtaining favorable feedback number 013/2017. A cross-sectional, exploratory, descriptive study was performed with a quantitative approach, with 17 family health teams, on the west area of the city of Rio Grande, Brazil. The sample was constituted by 350 elderly people. Data was collected from July to December, 2017, through two instruments: a sociodemography and health characterization one, and an adapted and translated version of the Short Test of Functional Health Literacy in Adults, which verified the health literacy level. A statistical descriptive analysis was made, as well as a statistical inferential one, using ANOVA tests, chi-square test and a multiple linear regression. All ethical precepts of the 466/2012 Resolution were respected. Among the 350 elderly people interviewed, most were between 60 and 69 years old (64%), did not have a paid job (76.6%) and had family income higher than a minimum wage (63%). The average Functional Health Literacy mark was 51.9, which is inadequate, with at least 2 and at most 100 points in the scale. There was significant statistical relation between Functional Health Literacy and the variables of age, sex, education, income, chronic diseases, hospitalization rate, use of non-prescribed medication, doctor’s orders, no professional instruction, and use of internet, neighbors/friends/relatives, magazines/books and brochures as health source (p<0.005). The most frequent chronic diseases were hypertension, diabetes, cardiopathies and musculoskeletal disease. There was no significant statistical relation between Functional Health Literacy, health habits, chronic diseases and use of medication (p>0.005). The results of the study indicate that not only nurses, but every health professional should pay attention to the reasons for low Functional Health Literacy among elderly people, in order to minimize health impacts that could be caused by difficulty in understanding health instructions and thus compromise life quality and active aging of such population.